2004
DOI: 10.1002/cncr.20604
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia caused by Achromobacter and Alcaligenes species in 46 patients with cancer (1989–2003)

Abstract: ) for providing the microbiologic information presented in the current report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
165
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(181 citation statements)
references
References 23 publications
10
165
3
3
Order By: Relevance
“…Mortality was related to A. xylosoxidans infection in nine (22%) patients, which is similar to previous findings [20,21]. Aisenberg et al collaborators [20] revealed that sepsis syndrome and high APACHE II scores are predictors of an increase in 30-day mortality.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Mortality was related to A. xylosoxidans infection in nine (22%) patients, which is similar to previous findings [20,21]. Aisenberg et al collaborators [20] revealed that sepsis syndrome and high APACHE II scores are predictors of an increase in 30-day mortality.…”
Section: Discussionsupporting
confidence: 88%
“…Mortality was related to A. xylosoxidans infection in nine (22%) patients, which is similar to previous findings [20,21]. Aisenberg et al collaborators [20] revealed that sepsis syndrome and high APACHE II scores are predictors of an increase in 30-day mortality. Although the APACHE II score in the imipenem-resistant group (26.95 ± 8.02) was higher than that in the imipenem-nonresistant group (20.52 ± 6.06) (p < 0.05), there were no obvious differences in mortality (6 cases versus 3 cases).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was described in 1971 by Yabuuchi and Ohyama [1], who isolated it from purulent ear discharges from 7 patients with chronic otitis media. A.xylosoxidans has been isolated from a variety of human clinical sources, including blood, cerebrospinal fluid (CSF), sputum, peritoneal fluid, skin, ear discharge, wounds, abscesses, bone, joints, endocardium and central venous catheters [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%